Dysregulation of miR-155-5p and miR-200-3p and the Anti-Non-Bilayer Phospholipid Arrangement Antibodies Favor the Development of Lupus in Three Novel Murine Lupus Models - Luz Ángela Zárate-Neira; Sandra Sánchez-Barbosa; Abraham Pedroza-Torres; Albany Reséndiz-Mora; Carlos Wong; Isabel Baeza; Carlos Pérez-Plasencia; Carlos Wong-Baeza (Journal of Immunology Research)
Systemic lupus erythematosus (SLE) is characterized by deregulated activation of T and B cells, autoantibody production, and consequent formation of immune complexes. Liposomes with nonbilayer phospholipid arrangements (NPA), induced by chlorpromazine, procainamide, or manganese, provoke a disease resembling human lupus when administered to mice. These mice produce anti-NPA IgM and IgG antibodies and exhibit an increased number of TLR-expressing spleen cells and a modified gene expression associated with TICAM1-dependent TLR-4 signaling (including IFNA1 and IFNA2) and complement activation. Additionally, they showed a diminished gene expression related to apoptosis and NK cell activation. We hypothesized that such gene expression may be affected by miRNAs and so miRNA expression was studied. Twelve deregulated miRNAs were found. Six of them were common to the three lupus-like models. Their validation by qRT-PCR and TaqMan probes, including miR-342-3p, revealed that miR-155-5p and miR-200a-3p expression was statistically significant. Currently described functions for these miRNAs in autoimmune diseases such as SLE reveal their participation in inflammation, interferon production, germinal center responses, and antibody maturation. Taking into account these findings, we propose miR-155-5p and miR-200a-3p, together with the anti-NPA antibodies, as key players in the murine lupus-like models and possible biomarkers of the human SLE.